Digitalisierung - Subjekt - Bildung Kritische Betrachtungen der digitalen Transformation - Dander, Valentin; Bettinger, Patrick; Ferraro, Estella; Leineweber, Christian; Rummler, Klaus (Verlag Barbara Budrich, 2020)
The volume brings together critical perspectives on digital transformations and the underlying mechanisms such as quantification, algorithmization and commercialization. The authors from media pedagogy, educational science, educational research and media studies problematize tendencies of economist and technological appropriation and describe resistant practices. All of them are specifically concerned with the question of the complex relationship of the subject to society, institutions and media - and the possibilities of its change.